Evidence for the primacy of living root inputs, not root or shoot litter, in forming soil organic carbon - Sokol, Noah W.; Kuebbing, Sara. E.; Karlsen‐Ayala, Elena; Bradford, Mark A. (The New phytologist, 2019)
Soil organic carbon (SOC) is primarily formed from plant inputs, but the relative carbon (C) contributions from living root inputs (i.e. rhizodeposits) vs litter inputs (i.e. root + shoot litter) are poorly understood. Recent theory suggests that living root inputs exert a disproportionate influence on SOC formation, but few field studies have explicitly tested this by separately tracking living root vs litter inputs as they move through the soil food web and into distinct SOC pools. We used a manipulative field experiment with an annual C4 grass in a forest understory to differentially track its living root vs litter inputs into the soil and to assess net SOC formation over multiple years. We show that living root inputs are 2–13 times more efficient than litter inputs in forming both slow-cycling, mineral-associated SOC as well as fast-cycling, particulate organic C. Furthermore, we demonstrate that living root inputs are more efficiently anabolized by the soil microbial community en route to the mineral-associated SOC pool (dubbed ‘the in vivo microbial turnover pathway’). Overall, our findings provide support for the primacy of living root inputs in forming SOC. However, we also highlight the possibility of nonadditive effects of living root and litter inputs, which may deplete SOC pools despite greater SOC formation rates.